Population responses of farmland bird species to agri‐environment schemes and land management options in Northeastern Scotland. Issue 3 (3rd January 2019) - Daskalova, Gergana N.; Phillimore, Albert B.; Bell, Matthew; Maggs, Hywel E.; Perkins, Allan J.
Abstract: The decline of farmland birds across Europe is a well‐documented case of biodiversity loss, and despite land stewardship supported by funding from agri‐environment schemes (AES), the negative trends have not yet been reversed. To investigate the contribution of AES towards farmland bird conservation, we compared abundance of five farmland bird species across 13 years and 53 farms (158 farm years = AES, 72 farm years = non AES) in Northeastern Scotland (UK), a region with relatively mixed farmland. Between 2003 and 2015, on both AES and control farms, skylark ( Alauda arvensis ) showed a nonsignificant decline, and tree sparrow ( Passer montanus ) and yellowhammer ( Emberiza citrinella ) nonsignificant increases, whereas reed bunting ( Emberiza schoeniclus ) and linnet ( Carduelis cannabina ) populations remained relatively stable. We did not detect a significant association between AES and avian abundance or population trends for any of these species, but there were positive associations with some AES management options. Possible explanations for the lack of a significant AES‐bird abundance association include poor uptake of the best AES options for farmland birds, suboptimal implementation, spill‐over effects from AES onto control farms, and the relatively good state of farmland habitats outwith AES in Northeastern Scotland. Synthesis and applications . We documented a weak effect size of participation in agri‐environment schemes on farmland bird abundance. We therefore recommend future monitoring studies be designed after consulting a power analysis. Among different land management options, we found that species‐rich grasslands, water margins, and wetland creation enhanced breeding bird abundance, highlighting the importance of relatively undisturbed herbaceous or grassland vegetation for farmland conservation. Abstract : We documented a weak effect size of participation in agri‐environment schemes on farmland bird abundance. We therefore recommend future monitoring studies be designed after consulting a power analysis. Among different land management options, we found that species‐rich grasslands, water margins, and wetland creation enhanced breeding bird abundance, highlighting the importance of relatively undisturbed herbaceous or grassland vegetation for farmland conservation.